2017
DOI: 10.1007/s10531-017-1343-7
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of African chikanda cake highlights conservation challenges in orchids

Abstract: Chikanda is a traditional dish made with wild-harvested ground orchid tubers belonging to three orchidioid genera, Disa, Satyrium and Habenaria, all of which are CITES appendix II-listed. Identification of collected orchid tubers is very difficult and documentation of constituent species in prepared chikanda has hitherto been impossible. Here amplicon metabarcoding was used in samples of six prepared chikanda cakes to study genetic sequence diversity and species diversity in this product. Molecular operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Our DNA metabarcoding results corroborate previous research that used metabarcoding to authenticate herbal products (Coghlan et al, 2012, 2015; Cheng et al, 2014; Ivanova et al, 2016; Veldman et al, 2017). In this study we confirm its applicability to test for presence of V. officinalis and simultaneously to detect substitution, adulteration and/or admixture of other Veronica species.…”
Section: Resultssupporting
confidence: 88%
“…Our DNA metabarcoding results corroborate previous research that used metabarcoding to authenticate herbal products (Coghlan et al, 2012, 2015; Cheng et al, 2014; Ivanova et al, 2016; Veldman et al, 2017). In this study we confirm its applicability to test for presence of V. officinalis and simultaneously to detect substitution, adulteration and/or admixture of other Veronica species.…”
Section: Resultssupporting
confidence: 88%
“…In DNA barcoding and plant product identification and authentication projects it is common to work with degraded DNA substrates for which it might be difficult to use methylation enrichment or the full plastid genome as a barcoding strategy. However, alternatives such as target enrichment and amplicon sequencing are possible [64, 123125]. Here we have identified four variable regions that possess sufficient variation and genetic structure to discriminate most ginseng species.…”
Section: Discussionmentioning
confidence: 98%
“…When we look at the chikanda type known as kapapa for example, SJK44 contains Platycoryne crocea, whereas SJK11, which is supposed to be a mix of kasebelela and kapapa, only seems to contain Satyrium species. In case of other chikanda types there seems to be more consistency: myala or real chikanda referred to Disa robusta, D. welwitschii and Satyrium buchananii, mshilamshila samples between fake chikanda samples as well [19]. It is well-known from literature that local species concepts are not necessarily congruent with scientific classifications and that species might be subject to overor underdifferentiation [50,51].…”
Section: Local Versus Scientific Classification Of Chikandamentioning
confidence: 99%
“…[12,13], whereas recently at least 32 species belonging to the genera Brachycorythis, Disa, Eulophia, Habenaria, Roeperocharis and Satyrium were suggested to be used for chikanda production based on collections in the field [12,[14][15][16][17][18][19] and one metabarcoding study of ready-made chikanda cakes [19]. To date, however, no study identified the orchids traded at the local markets, since the tubers lack sufficient morphological characters for taxonomic identification to species level [8,19]. Local classification systems categorize the tubers based on texture, harvesting locality, soil colour and phenology, but these are not likely to be congruent with scientific classifications [6,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation